Near-tropical Early Eocene terrestrial temperatures at the Australo-Antarctic margin, western Tasmania - Carpenter, RJ; Gregory Jordan; Macphail, MK; Hill, RS (2012)
A worldwide greenhouse warm climate prevailed in the Early Eocene, and nowhere was warming more dramatic than at high latitudes. Sea-surface temperatures of ~34 °C have been estimated for a site at paleolatitude 65°S on the East Tasman Plateau of the southwest Pacifi c Ocean, but these estimates require independent validation, including from terrestrial proxies. Here we determine a near-tropical terrestrial mean annual temperature estimate of ~24 °C at sea level for an Early Eocene site in Tasmania, Australia, using three proxies based on welldated estuarine plant fossils. This estimate is lower than the nearby sea estimates to the east, but similarly suggests that, as in the southwest Pacifi c, Early Eocene climates in the eastern Australo-Antarctic region were warmer than inferred elsewhere at high latitudes, including on the Antarctic Peninsula. Such data are essential for improving our understanding of climatic and biotic evolution in the Southern Hemisphere.